The determinants and significance of intraluminal stent protrusion in patients with acute myocardial infarction. (14th October 2021) - Zalewski, J; Molek, P; Machnik, A; Stepien, K; Nawrotek, B; Nowak, K; Nowak, G; Tomala, M; Legutko, J; Nessler, J; Undas, A
Abstract: Background: The mchanisms leading to intraluminal stent protrusion in patients following primary coronary angioplasty for ST-elevation myocardial infarction (STEMI) are not fully elucidated. Purpose: We sought to investigate composition of stent protrusion, its systemic and local determinants as well as its consequences for epicardial blood flow restoration in STEMI patients. Methods: We enrolled 85 STEMI patients with median age 61 (interquartile range 54–69) years. In all patients optical coherence tomography of an infarct-related artery was performed first following epicardial blood flow restoration after aspiration thrombectomy and second after final stent deployment. On admission, besides standard laboratory investigations we measured calibrated automated thrombogram parameters including time to start clotting, time to peak thrombin generation, peak thrombin generation and endogenous thrombin potential as well as ex vivo measured fibrin clot permeability reflecting fibrin pore size and fibrin clot lysis time. Results: A median volume of stent protrusion was 13.4 (8.5–25.4) mm 3 while atherothrombotic burden defined as a ratio of free intraluminal thrombus and tissue protrusion divided by stent volume was 6 (3.9–7.5)%. The main component of stent protrusion was lipid tissue in 32 (37.6%), fibrous tissue in 27 (31.8%) and thrombus in 26 (30.6%) patients. A volume of stent protrusion was correlated with total stent volume (R=0.79, P<0.001) and the length of lipid reach pool in the naïve coronary vessel intima (R=0.31, P=0.007) whereas atherothrombotic burden was correlated with residual thrombus volume before stent implantation (R=0.34, P=0.003), arcus of maximal lipid reach pool in the naïve coronary vessel intima (R=0.25, P=0.03) and stent area (R=0.26, P=0.02). The residual thrombus volume after aspiration thrombectomy was correlated with clot permeability (R=0.024, P=0.04) and inversely correlated with time to peak thrombin generation (R=−0.23, P=0.04). A temporary deterioration of epicardial blood flow of at least 1 point in Thrombolysis in Myocardial Infarction scale following stent implantation detected in 20 (23.5%) patients was associated with shorter lag time (3.0 [2.7–3.3] vs. 3.3 [3.0–4.0] min, P=0.015), shorter time to peak thrombin generation (5.7 [5.3–6.1] vs. 6.3 [5.7–7.1] min, P=0.026) and more frequent presence of lipid-rich stent protrusion (65 vs. 29%, P=0.007) as compared to the patients without slow-flow phenomenon after stent deployment. Conclusions: The total volume of stent protrusion is correlated with local determinants including stent size and lipid content in the naïve coronary artery intima. After adjustment for stent volume, atherothrombotic burden is additionaly affected by residual thrombus volume after aspiration thrombectomy. However, patients with faster thrombin formation and lipid-rich stent protrusion are more prone to slow-flow phenomenon following stent implantation. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Science Center of Poland